Reliability of Isokinetic Strength Assessments of Knee and Hip Using the Biodex System 4 Dynamometer and Associations With Functional Strength in Healthy Children - van Tittelboom, Vanessa; Alemdaroglu-Gürbüz, Ipek; Hanssen, Britta; Heyrman, Lieve; Feys, Hilde; Desloovere, Kaat; Calders, Patrick; Van den Broeck, Christine (Frontiers in Sports and Active Living, 2022)
Background This study aimed to analyze the reliability of concentric isokinetic strength assessments (knee and hip) using the Biodex System 4 in healthy children and assess the association with functional strength tests (sit-to-stand [STS], lateral-step-up [LSU]). Methods 19 children (6–12 years) were included. Knee and hip flexion and extension, and hip abduction and adduction were tested at 60 and 90°/s. Results Relative and absolute reliability at 60°/s tended to show better results compared to those at 90°/s. Intra class correlations (ICCs) of knee flexion and extension at 60°/s were good (0.79–0.89). For hip flexion, extension, abduction and adduction at 60°/s ICCs were moderate to good (0.53–0.83). The smallest detectable change (SDC) values (expressed in %) were highly variable. The SDC% for knee flexion and extension and hip abduction at 60°/s were around 50%. Positive associations were found between hip extension and abduction isokinetic strength and the STS test. Conclusion Concentric isokinetic strength assessments in healthy children using the Biodex System 4 were found reliable for knee flexion and extension and hip abduction. Limited associations were found between concentric isokinetic strength tests and functional strength tests.